1999
DOI: 10.1002/(sici)1096-8628(19990903)86:1<71::aid-ajmg14>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase thermolabile variant and oral clefts

Abstract: Folic acid can prevent neural tube defects; in some cases the mechanism is probably a correction of a metabolic defect caused by thermolabile methylenetetrahydrofolate reductase (MTHFR) found in increased frequency in cases. It is less clear whether folic acid can prevent oral clefts, in part because it is not known whether thermolabile MTHFR is more common in those with oral clefts. This study examined the prevalence of the mutation (677 C-->T) that causes thermolabile MTHFR in subjects with oral clefts from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 15 publications
0
45
2
2
Order By: Relevance
“…In this regard, using the case-control design, Tolarova et al [88] first observed that homozygotes for the 677 T allele were three times more frequent in CL/P Argentinean patients than in controls. However, these findings were not confirmed by most of the subsequent studies using California [89], Brazil [90], Polish [91] and Irish [92] population samples. However, in an, homozygosity for the C677T allele was associated with an increased risk for isolated cleft palate (OR =3.2; 95 percent CI: 1.3, 7.9) and possibly for cleft lip with or without cleft palate (OR =1.6; 95 percent CI: 0.8, 3.4) [92].…”
Section: Association Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…In this regard, using the case-control design, Tolarova et al [88] first observed that homozygotes for the 677 T allele were three times more frequent in CL/P Argentinean patients than in controls. However, these findings were not confirmed by most of the subsequent studies using California [89], Brazil [90], Polish [91] and Irish [92] population samples. However, in an, homozygosity for the C677T allele was associated with an increased risk for isolated cleft palate (OR =3.2; 95 percent CI: 1.3, 7.9) and possibly for cleft lip with or without cleft palate (OR =1.6; 95 percent CI: 0.8, 3.4) [92].…”
Section: Association Studiesmentioning
confidence: 63%
“…However, these findings were not confirmed by most of the subsequent studies using California [89], Brazil [90], Polish [91] and Irish [92] population samples. However, in an, homozygosity for the C677T allele was associated with an increased risk for isolated cleft palate (OR =3.2; 95 percent CI: 1.3, 7.9) and possibly for cleft lip with or without cleft palate (OR =1.6; 95 percent CI: 0.8, 3.4) [92]. An increased risk due to the maternal MTHFR genotype (677 T or 1282A alleles) on predisposition to CL/P was suggested by several studies [14,93,94,95,96].…”
Section: Association Studiesmentioning
confidence: 63%
“…The T allele frequency of 3.9% did not differ from the frequency in the general Brazilian population (Arruda et al, 1998). Previous studies on the association between C677T polymorphism and NS-CL/P produced contradictory results (Shaw et al, 1995(Shaw et al, , 1996(Shaw et al, , 1998Tolarova and Cervenka, 1998;Gaspar et al, 1999;Mills et al, 1999;Blanton et al, 2000Blanton et al, , 2002Wyszynski and Diehl, 2000;Martinelli et al, 2001;Prescott et al, 2002;van Rooij et al, 2003).…”
mentioning
confidence: 73%
“…The etiology is complex, including multiple genetic and environmental factors. The MSX1 and TGFB3 genes have been suggested as candidate genes based on animal models (Satokata and Maas, 1994;Kaartinen et al, 1995;Proetzel et al, 1995) and association studies in humans with genes MSX1, TGFB3 and MTHFR have pointed to the involvement of these genes in NS-CL/P etiology (Maestri et al, 1997;Lidral et al, 1998;Romitti et al, 1999;Mills et al, 1999; Wyszynsky and Diehl, 2000;Beaty et al, 2001). The MSX1 gene maps to chromosome 4p16.…”
mentioning
confidence: 99%
“…Animal studies suggest that a decreased conversion of homocysteine to methionine could be a crucial step in causing neural tube defects. It has been shown that rat embryos in culture require methionine for neural tube closure (Mills et al, 1999).…”
Section: Approximatelymentioning
confidence: 99%